Epidemiologic study on survival of chronic myeloid leukemia and Ph(+) acute lymphoblastic leukemia patients with BCR-ABL T315I mutation - Nicolini, Franck E. (Blood, 2009)
The BCR–ABL T315I mutation represents a major mechanism of resistance to tyrosine kinase inhibitors (TKIs). The objectives of this retrospective observational study were to estimate overall and progression-free survival for chronic myeloid leukemia in chronic-phase (CP), accelerated-phase (AP), or blastic-phase (BP) and Philadelphia chromosome—positive (Ph)(+) acute lymphoblastic leukemia (ALL) patients with T315I mutation. Medical records of 222 patients from 9 countries were reviewed; data were analyzed using log-rank tests and Cox proportional hazard models. Median age at T315I mutation detection was 54 years; 57% cases were men. Median time between TKI treatment initiation and T315I mutation detection was 29.2, 15.4, 5.8, and 9.1 months, respectively, for CP, AP, BP, and Ph(+) ALL patients. After T315I mutation detection, second-generation TKIs were used in 56% of cases, hydroxyurea in 39%, imatinib in 35%, cytarabine in 26%, MK-0457 in 11%, stem cell transplantation in 17%, and interferon-α in 6% of cases. Median overall survival from T315I mutation detection was 22.4, 28.4, 4.0, and 4.9 months, and median progression-free survival was 11.5, 22.2, 1.8, and 2.5 months, respectively, for CP, AP, BP, and Ph(+) ALL patients. These results confirm that survival of patients harboring a T315I mutation is dependent on disease phase at the time of mutation detection.